The symptom burden of treatment‐naive patients with head and neck cancer. Issue 5 (4th November 2014) - Hanna, Ehab Y.; Mendoza, Tito R.; Rosenthal, David I.; Gunn, G. Brandon; Sehra, Pamela; Yucel, Emre; Cleeland, Charles S.
<x xml:space="preserve">Abstract</x> BACKGROUND The treatment of head and neck cancer (HNC) may cause substantial local and systemic symptomatic morbidities, but many patients have high symptom levels before treatment begins. Knowledge of disease‐related (treatment‐naive) symptom status would aid in the evaluation of the symptomatic benefit or burden of HNC therapies. METHODS The authors retrospectively examined symptoms, quality of life, and health status reported by patients with HNC who were naive to any treatment. Symptoms were explored by anatomical site and disease factors were correlated with symptom severity and interference. A clustering algorithm was used to identify a subset of highly symptomatic patients, and the effects of disease site, tumor stage, and demographic variables on membership in this high‐symptom group were examined. RESULTS A total of 748 treatment‐naive patients with mucosal (434 patients), nonmucosal (272 patients), or skull base (42 patients) tumors were identified who had rated their symptoms using the MD Anderson Symptom Inventory. The majority of patients were white non‐Hispanic (82%) and male (68%), with a median age of 59 years. Approximately one‐third the patients had a high pretreatment symptom burden. Pain, fatigue, distress, and disturbed sleep were the most severe symptoms reported, regardless of tumor stage or site. Symptom burden was found to be higher among patients with more advanced disease. Predictors of a high symptom burden included having a mucosal tumor and being female. CONCLUSIONS The high prevalence of moderate to severe symptoms found in the current study demonstrates the importance of assessing patient‐reported symptoms routinely before treatment is initiated and emphasizes the need for symptom management in parallel with disease treatment. Baseline characterization of symptom status should be incorporated into clinical trials that may affect symptom burden. Cancer 2015;121:766–773. © 2014 American Cancer Society.